A Three-Layer Privacy Preserving Cloud Storage Scheme Based on DNA Computing with Morse code and Zigzag Pattern - Chauhan, Puransingh; Syeda, Rana (International Journal of Computer Sciences and Engineering, 2025)
With the rapid development of network bandwidth, the volume of user’s data is rising geometrically. User’s requirement cannot be satisfied by the capacity of local machine any more. Therefore, people try to find new methods to store their data. Pursuing more powerful storage capacity, a growing number of users select cloud storage. Storing data on a public cloud server is a trend in the future and the cloud storage technology will become wide spread in a few years. Cloud storage is a cloud computing system which provides data storage and management service. With a cluster of applications, network technology and distributed file system technology, cloud storage makes a large number of different storage devices work together coordinately. Nowadays there are a lot of companies providing a variety of cloud storage services, such as Dropbox, Google Drive, iCloud, Amazon Web Services, etc. These companies provide large capacity of storage and various services related to other popular applications, which in turn leads to their success in attracting humorous subscribers. However, cloud storage service still exists a lot of security problems. The privacy problem is particularly significant among those security issues. In history, there were some famous cloud storage privacy leakage events. For example, in 2018 despite a robust legislation on data protection by UIDAI, Aadhaar numbers and bank details of over 134,000 beneficiaries on Andhra Pradesh Housing Corporation's website have been leaked. Apples iCloud leakage event in 2014, numerous Hollywood actresses private photos stored in the clouds were stolen. This event caused an uproar, which was responsible for the users’ anxiety about the privacy of their data stored in cloud server.